HOW SOCIAL MEDIA MARKETING AND BRAND AWARENESS AFFECT CONSUMER PURCHASE DECISIONS: AN EMPIRICAL STUDY OF CAHAYA MEGAH T-SHIRT? - Sudrajat, Jajat; Mubarok, Dadan Abdul Aziz (Universitas Muhammadiyah Tangerang, 2025)
This study addresses the urgency of understanding how digital marketing strategies influence consumer behavior in the competitive apparel industry, particularly focusing on Small and Medium Enterprises (SMEs). The research aims to analyze the effects of Social Media Marketing (SMM) and Brand Awareness (BA) on consumer purchase decisions for Cahaya Megah T-Shirt. Employing a quantitative descriptive and verificative approach, data were collected through questionnaires distributed to 100 respondents using the Slovin formula. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination, and t-tests. The results indicate that both Social Media Marketing and Brand Awareness have a significant positive impact on consumer purchase decisions, with Brand Awareness showing a stronger influence. This research contributes to the existing body of knowledge by providing empirical evidence specific to the Indonesian SME context and offers practical insights for business owners to optimize their digital marketing investments and enhance brand strategies to drive consumer purchasing behavior.